2003
DOI: 10.1103/physreva.68.052312
|View full text |Cite
|
Sign up to set email alerts
|

Generation of entangled states of two atoms inside a leaky cavity

Abstract: An in-depth theoretical study is carried out to examine the quasi-deterministic entanglement of two atoms inside a leaky cavity. Two Λ-type three-level atoms, initially in their ground states, may become maximally entangled through the interaction with a single photon. By working out an exact analytic solution, we show that the probability of success depends crucially on the spectral function of the injected photon. With a cavity photon, one can generate a maximally entangled state with a certain probability t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…The atoms become maximally entangled if the emitted photon is right-circularly polarized, or otherwise remain intact. The probability of success of the entangling process is shown to approach unity if the input photon is quasi-monochromatic [21]. It is worthwhile to remark that other fundamental processes in quantum computing like quantum state-swapping and controlled phase-flip gates can also be achieved with high success rates via CQED interaction between atoms and such quasi-monochromatic single photons [26,27].…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…The atoms become maximally entangled if the emitted photon is right-circularly polarized, or otherwise remain intact. The probability of success of the entangling process is shown to approach unity if the input photon is quasi-monochromatic [21]. It is worthwhile to remark that other fundamental processes in quantum computing like quantum state-swapping and controlled phase-flip gates can also be achieved with high success rates via CQED interaction between atoms and such quasi-monochromatic single photons [26,27].…”
Section: Introductionmentioning
confidence: 95%
“…Being a well-studied topic in quantum optics, cavity quantum electrodynamics (CQED) provides a full arsenal of techniques to generate entangled atom pairs [18][19][20][21][22] and also entangled photon pairs [23,24]. In particular, previous studies have shown that cavity loss as well as environmental noise can help to generate entanglement and increase the success rate [19,21,22,25]. However, most of these schemes referred above are probabilistic.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations